Eksplorasi Etnomatika Pada Pakaian Adat Dayak Terkait Geometri Bidang Datar - Setia Widia Rahayu; Hendi Santosa (Lembaga Bale Literasi, 2026)
This study aims to describe the mathematical elements found in the traditional clothing of the Dayak Kenyah tribe, particularly the Ta’a and Sapei Sapaq attire. This research employs a case study approach, with data collected through observation, interviews, and documentation. This approach allows the researcher to explore in depth the activities, processes, and meanings embedded in the research object. The results indicate that various mathematical concepts are integrated into the motifs and patterns of the traditional clothing. The identified mathematical elements include plane geometric shapes such as triangles, rectangles, and circles. In addition, concepts of plane geometry such as symmetry and pattern repetition were also found, reflecting order and mathematical structure in the clothing design. These findings demonstrate that traditional clothing holds not only aesthetic and cultural values but also mathematical concepts that can be utilized as contextual learning resources. This study is expected to contribute to the development of ethnomathematics and serve as an alternative approach to making mathematics learning more meaningful and relevant to everyday life.